Non-equilibrium vibrational and electron energy distributions functions in atmospheric nitrogen ns pulsed discharges and μs post-discharges: the role of electron molecule vibrational excitation scaling-laws. (29th April 2015) - Colonna, Gianpiero; Laporta, Vincenzo; Celiberto, Roberto; Capitelli, Mario; Tennyson, Jonathan
Abstract: The formation of the electron energy distribution function in nanosecond atmospheric nitrogen discharges is investigated by means of self-consistent solution of the chemical kinetics and the Boltzmann equation for free electrons. The post-discharge phase is followed to few microseconds. The model is formulated in order to investigate the role of the cross section set, focusing on the vibrational-excitation by electron-impact through resonant channel. Four different cross section sets are considered, one based on internally consistent vibrational-excitation calculations which extend to the whole vibrational ladder, and the others obtained by applying commonly used scaling-laws.